The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/pola.20482
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of the single electron transfer–degenerative chain transfer mediated living radical polymerization (SET–DTLRP) of vinyl chloride in water at 25 °C

Abstract: The accelerated single electron transfer–degenerative chain transfer mediated living radical polymerization (SET–DTLRP) of vinyl chloride (VC) in H2O/tetrahydrofuran (THF) at 25 °C is reported. This process is catalyzed by sodium dithionite (Na2S2O4)‐sodium bicarbonate (NaHCO3). Electron transfer cocatalysts (ETC) 1,1′‐dialkyl‐4,4′‐bipyridinum dihalides or alkyl viologens were also employed in this polymerization. The resulting poly(vinyl chloride) (PVC) has a number‐average molecular weight (Mn) = 2,000–12,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 17 publications
5
71
2
Order By: Relevance
“…[44][45][46][47] In light of the theory proposed here it may be as a result of the reduced transient radical lifetime that defects, which for vinyl chloride polymerization are largely caused by transfer to polymer, are reduced. In addition, similar polymerizations conducted in aqueous media suggested that chain transfer to the poly(vinyl alcohol) stabilizer employed does not occur.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47] In light of the theory proposed here it may be as a result of the reduced transient radical lifetime that defects, which for vinyl chloride polymerization are largely caused by transfer to polymer, are reduced. In addition, similar polymerizations conducted in aqueous media suggested that chain transfer to the poly(vinyl alcohol) stabilizer employed does not occur.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of NMR experiments and techniques was undertaken in order to interpret the peaks disclosed in the a) b) [36] The peaks in the region of 3.7-3.9 ppm can be attributed to the CH 2 Cl which is a component of the CH 2 ClCH 2 -group. [36] This group may be introduced in the polymer by the initiator radical or as a result of branching of the polymer.…”
Section: Structural Determination Of the Polymermentioning
confidence: 99%
“…[36] This group may be introduced in the polymer by the initiator radical or as a result of branching of the polymer. The peaks in the region of 4.2-4.8 ppm correspond to the main chain CHCl group.…”
Section: Structural Determination Of the Polymermentioning
confidence: 99%
“…5 Nevertheless, the stringent conditions associated to some of these methods have limited the perspectives for widespread of commercial products. After several years of the development, Percec et al discovered a new strategy to polymerize-activated [6][7][8] and nonactivated monomers, [9][10][11] under controlled/ living mechanism in aqueous medium. In addition, this method requires only industrially consumed compounds and lead to a polymer that does not need to be purified.…”
Section: Introductionmentioning
confidence: 99%